A gender assessment on the main opportunities and stumbling blocks that women face relating to agriculture and agribusiness in Malawi - Greehy, P.; Enokenwa Baa, Ojongetakah; Nortje, Karen (International Water Management Institute (IWMI), 2024)
Objective: This research explores the multifaceted challenges and opportunities faced by women in Malawi's agricultural and agribusiness sectors.